2013
DOI: 10.1371/journal.pone.0060394
|View full text |Cite
|
Sign up to set email alerts
|

The Tolerogenic Peptide, hCDR1, Down-Regulates the Expression of Interferon-α in Murine and Human Systemic Lupus Erythematosus

Abstract: BackgroundThe tolerogenic peptide, hCDR1, ameliorated manifestations of systemic lupus erythematosus (SLE) via the immunomodulation of pro-inflammatory and immunosuppressive cytokines and the induction of regulatory T cells. Because type I interferon (IFN-α) has been implicated to play a role in SLE pathogenesis, we investigated the effects of hCDR1 on IFN-α in a murine model of SLE and in human lupus.Methodology/Principal Findings(NZBxNZW)F1 mice with established SLE were treated with hCDR1 (10 weekly injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…Preliminary studies in humans confirmed data from animal models showing that edratide downregulates pathogenic cytokines and apoptosis, IFN-a gene expression, and upregulates immunosuppressive molecules and Tregs cells in peripheral blood [29][30][31].…”
Section: Edratidementioning
confidence: 86%
“…Preliminary studies in humans confirmed data from animal models showing that edratide downregulates pathogenic cytokines and apoptosis, IFN-a gene expression, and upregulates immunosuppressive molecules and Tregs cells in peripheral blood [29][30][31].…”
Section: Edratidementioning
confidence: 86%
“…Immunoglobulin G has been known to exhibit tolerogenic properties for decades, and a number of previous publications have alluded to the potential presence of regulatory or “suppressor” epitopes in IgG constant domains, whether located to the constant (Fc) or binding region (Fab). For example, Baxevanis et al described a tolerizing effect of Ig Fc that was localized to the CH2 region, consistent with the location of several Tregitopes [ 15 ]; a peptide isolated from the Fab region of an anti-idiotypic peptide (which overlaps one of the subsequently identified Tregitopes) suppressed Systemic Lupus Erythematosis in humans and in mice [ 16 , 17 ]; a peptide derived from the highly conserved J region framework was shown by Warnke et al to induce Tregs to expand and suppress immune responses in suppressor assays [ 18 ].…”
Section: Tregitopes: What Are They?mentioning
confidence: 89%
“…Waisman et al reported that peptides from CDRs of pathogenic anti-DNA mAbs could prevent autoantibody production and downregulate autoreactive T cell responses, representing a potential treatment for SLE [184,185]. Several other studies further revealed that a tolerogenic peptide derived from the CDR1 of a human anti-DNA autoantibody (hCDR1) could ameliorate lupus by inducing Tregs and suppressing the activation of autoreactive cells in lupus animal models [186,187]. Several possible mechanisms have also been proposed to explain the therapeutic role of hCDR1 in SLE, such as TGF-β-mediated suppression of autoreactive T cells and downregulation of transcription factors responsible for negative regulation of T cell activation [188,189].…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%